Prayers from the Inner City: Listening to the Prayer Board in Southwark Cathedral - Siô, Tania ap (Research in the social scientific study of religion, 2015)
Although there are numerous empirical studies of the practice of prayer among ordinary people, there have been far fewer empirical studies exploring the content of personal prayer and the influence of location and situation on what people pray. The ap Siôn Analytic Framework for Intercessory Prayer (apSAFIP) model was developed to enable multiple studies to be conducted within different church-related contexts with a view to addressing this issue. This study presents an analysis of 958 prayer requests posted on the prayer board of Southwark Cathedral in London, uk, using the apSAFIP model which distinguishes among prayer intention, prayer reference and prayer objective. The results are compared with other cathedral prayer studies that have employed the same analytic tool, using ‘ordinary theology’ as an interpretative lens.